PERBANDINGAN POLA ASUH AYAH TUNGGAL DAN IBU TUNGGAL TERHADAP PERILAKU ANAK - Fernanda, Mutiara Heidi; Kustati, Martin; Bashori (As-Sulthan Journal of Education, 2025)
Families with single parents face numerous challenges in fulfilling their parenting roles. The parenting styles implemented by single parents have a highly significant influence on their children's behavior. This study aims to analyze and review the comparison of parenting styles between single fathers and single mothers regarding child behavior. The methodology employed in this research is a literature review, focusing on theoretical and conceptual analysis based on relevant written sources rather than requiring field data. The findings indicate that parenting styles vary among all parents. However, a significant comparison exists in the parenting approaches of single parents. Single mothers tend to place greater emphasis on emotional needs and closeness, often showing a propensity to apply an authoritarian parenting style, which is often a response to extreme double burdens. Meanwhile, single fathers tend to prioritize independence and problem-solving skills, adopting either a permissive or authoritative parenting style. However, single fathers frequently encounter difficulties in meeting the emotional needs of their children.